Implementation of Green Innovation, Supply Chain Management and Technology Capability on Business Performance of Micro, Small and Medium Enterprises - Mardikaningsih, Rahayu (PT ARRUS Intelektual Indonesia, 2024)
Entrepreneurship has been recognized as a mechanism for generating economic benefits. However, due to the emergence of the concept of business performance as a pressing issue affecting the global system today, it has been proposed that MSMEs, which stands for micro, small and medium enterprises, should also be given special attention. Therefore, this study intends to investigate the viewpoints of MSME entrepreneurs from green innovation, supply chain management, and technological capability to business performance in micro, small, and medium-sized enterprises (MSMEs). The study adopted a quantitative approach and involved multiple linear regression analysis tools. This study targets a population of 100 MSMEs operating in Surabaya City. Accidental sampling will be used for sampling. The study results indicate that green innovation has a significant positive impact on MSME business performance. This innovation involves the implementation of practices that support environmental sustainability, such as the utilization of environmentally friendly materials, effective waste management, and green measures. In addition, the study also shows that efficiency in supply chain management and a high level of technological capability also contribute significantly to MSME business performance.